Effect of Actaplanin on performance of grazing steers - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1984)
Feeding actaplanin in a loose mineral mix or twice weekly in a supplement significantly improve gains of grazing steers. The greatest improvement in performance was found with average daily actaplanin intakes of 255 or 257 mg per head in the two trials.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Performance; Steers; Gain